Dinamika Pemekaran Wilayah Nagari Rabi Jonggor Kabupaten Pasaman Barat: Dynamics of Jurisdictive Boundary Realignment of Nagari Rabu Jonggor, Pasaman Barat District - Diah wahyuningsih; Zuly Qodir; Tengku Imam Syarifuddin (JOURNAL OF GOVERNMENT SCIENCE, 2020)
This article examines the dynamics of jurisdictive village boundary realignment of Nagari Rabi Jonggor, Pasaman Barat District, West Sumatra. This research employs bibliographical study by examining and analyzing various references relating to such issue and observing its dynamics, village budget allocation, the division of customary lands, the establishment of customary organization, and the practices of Nagari (village) government. As well, this article sketches the advangages and disadvantages of the remapping of such village administrative areas.  Keywords: administrative areas, boundary realignment, Nagari Rabi Jonggor.